What are the implications of South Africa's Protection of Investment Act on the SADC regions' aims to harmonise investment policy within the region, and how can possible inconsistencies and challenges be overcome? - Khiba, Motselisi (Department of Commercial Law, 2021)
Pre-Democratic South Africa was largely an isolated State. With the exceptions of the automotive and textile sectors, the country did not attract significant foreign investment due to the economic sanctions imposed by the international community in response to the crimes of apartheid. Between 1993 and 1995, the newly elected democratic government of South Africa concluded its first bilateral investment agreements with European countries. These bilateral investment agreements were made the standard for future treaties. The newly elected government realised the importance of foreign direct investment for achieving its economic growth and development objectives. Moreover, the conclusion of several bilateral investment treaties was used to strengthen relations with other countries and a tool to promote investment. However, by the late 1990s the South-African government found that these treaties were no longer appropriate. They often conflicted with the States socio-economic development policies and presented unequal protections for foreign investors and the States national policies. The Piero Foresti case, in which Italian investors brought an international arbitration claim against the South African government, galvanized the investment policy review process. The policy recommendation stemming from the review process included; that the South African cabinet refrain from entering into new bilateral investment treaties (BITs) - unless there were compelling political or economic reasons to do so, terminate existing BITs and replace them with domestic legislation. This dissertation considers the impact of the change in South Africa's investment policy on the Southern African Development Community (SADC) regions' efforts to harmonise investment policy across member states. It is an empirical study which considers South Africa's policy shift within the international investment law global context. Given South Africa's powerful andsomewhat hegemonic position on the African continent and within the region, whatever changes take place internally, are bound to spill-over into the region and potentially across the continent. The regional impact is analysed and described in detail. The research encompasses broader regional integration challenges, relations among member states and implications for dispute resolution. The study concludes that South Africa's policy shift is in line with global developments. It is an attempt to find a balance between investor protection and the States' ability to regulate. However, the policy shift has created a measure uncertainty regarding the settlement investment disputes within South Africa and across the SADC region. Furthermore, the broader obstacles which inhibit regional integration across SADC need to be addressed in order to facilitate investment policy harmonisation.